Instructional System Design Dalam Penyusunan Bahan Ajar Pendidikan Agama Islam Di MA Miftahul Huda Gorontalo Utara - Hakeu, Febrianto; Mobonggi, Arten H.; Mariana, Ana (Yayasan Rahmat Islamiyah, 2024)
This research includes qualitative research using documentation methods. The author's data source is obtained from the literature with data collection techniques using finding and documentation techniques. The data analysis model carried out by the author is a content analysis that is deductive and inductive. This research aims to describe the Instructional design system or known as learning design, and its application in the preparation of teaching materials. Instruction System Design or Learning Design Activities is a process to carry out a systematic learning workflow by analyzing student learning needs, analyzing how to meet learning needs and how to learn students both in terms of strategies and methods. Application of Instructional System Design In making teaching material for learning must be based on the Instructional system design so that the teaching materials created are not only teaching materials that are always repeated birthday after year without any novelty in the teaching materials made. So it can be concluded that the validity of the application of Instructional system design in making teaching materials is still very lacking and even rarely done by educators in preparing teaching materials to be used. Â